2006
DOI: 10.1111/j.1740-8261.2006.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

ULTRASONOGRAPHY OF THE LIVER, SPLEEN, AND URINARY TRACT OF THE CHEETAH (ACINONYX JUBATUS)

Abstract: Diseases of the abdomen of the cheetah (Acinonyx jubatus) include those affecting the liver, spleen, and urinary tract. The most common diseases of captive-bred cheetah are gastritis, gastric ulceration, glomerulosclerosis, and hepatic veno-occlusive disease, and are the most frequent causes of mortality in these animals. The purpose of this study was to describe the ultrasonographic anatomy of the normal liver, spleen, kidney, and urinary bladder of the anesthetized captive-bred cheetah. Twenty-one cheetahs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
30
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 35 publications
(61 reference statements)
9
30
2
Order By: Relevance
“…The echogenicity of the spleen, mostly hyperechoic in relation to the liver and renal cortices, was observed in this study and also has been observed in cheetahs (Acinonyx jubatus) 4 and domestic cats and dogs. 12 The triangular-shaped spleen surrounded by a thin smooth echogenic capsule that was observed in caracals is similar to the sonographic appearance of the spleen in domestic cats and dogs.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The echogenicity of the spleen, mostly hyperechoic in relation to the liver and renal cortices, was observed in this study and also has been observed in cheetahs (Acinonyx jubatus) 4 and domestic cats and dogs. 12 The triangular-shaped spleen surrounded by a thin smooth echogenic capsule that was observed in caracals is similar to the sonographic appearance of the spleen in domestic cats and dogs.…”
Section: Discussionsupporting
confidence: 85%
“…The presence and absence of contact between the right kidney and the right lobe of the liver that was observed in caracals also has been observed in cheetahs 4 and was attributed to the longer attachment of the kidneys similar to domestic cats. 8 The hyperechoic renal cortices compared with the medulla and good corticomedullary distinction are similar to the sonographic appearance of the kidneys in domestic cats and dogs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Unlikely to the described in marmosets that exhibit a poor corticomedullary definition (Wagner & Kirberger 2005), in crab-eating foxes this feature is well defined and the kidney presents a corticomedullary ratio of 1:1, similarly to the reported in cheetahs (Carstens et al 2006), dogs and cats (Silva et al 2008) and coatis (Ribeiro et al 2013). In Veterinary Medicine this proportion is important for the diagnosis of kidney diseases that may present an increased cortical echogenicity with enhanced or loss of corticomedullary definition (Nyland et al 2002).…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, ultrasonographic imaging proved to be effective to correlate anatomic and ultrasonographic features of abdominal organs, highlighting important characteristics considered normal for the species. Nevertheless, this method demonstrated to be a standard tool for diagnosis and clinical evaluation of crab-eating foxes, similarly to the described for ferrets (Mustela furo) (Neuwirth et al 1997), common marmoset (Callithrix jacchus) (Wagner & Kirberger 2005), cheetahs (Acinonyx jubatus) (Carstens et al 2006), tufted capuchin (Cebus apela) (Alves et al 2007) and coatis (Nasua nasua) (Ribeiro et al 2013). …”
Section: Discussionmentioning
confidence: 68%